Being an E-Teacher: Preparing the ESL Teacher to Teach English with Technology - Ismail Anas; Andi Musdariah (Journal of English Language Teaching and Linguistics, 2018)
In response to the extensive use of technology in the field of education particularly in English language teaching (ELT) context, both the pre-service and in-service ESL teachers are expected to use ICT tools in their teaching and learning environment. It is important to have a closer look at the use of ICT tools and the ease of access to the internet to see the opportunities to harness the technology resources for effective blended learning. Recently, although many studies revealed merely to promote the student’s self-directed learning and the successful of CALL, it is the teacher as a key role to blend such technologies into an effective teaching strategy. This study strives to develop a conceptual framework for teaching English with technology.  The framework delineates six perennial aspects of e-teacher development; they are; (1) teacher technology competency, (2) professional use of ICT tools, (3) professional use of the Internet, (4) web-based technology skills, (5) ESL teacher’s digital literacy, and (6) ESL materials and resources development.  This concept will bring many contributions to the way ESL teacher exploit the technology resources for an adaptive and interactive teaching strategy.  This paper also provides the implications for the practice, teacher, and student